Large-scale database analysis of anomalous thermal conductivity of quasicrystals and its application to thermal diodes - Takashi Kurono; Jinjia Zhang; Yasushi Kamimura; Keiichi Edagawa (Science and Technology of Advanced Materials: Methods)
One long-standing and crucial issue in the study of quasicrystals has been to identify the physical properties characteristic of quasicrystals. The large positive temperature coefficient of thermal conductivity at temperatures above room temperature, which has been observed in several quasicrystals, is one such characteristic property. Here, we show that this is indeed a very distinct property of quasicrystals through analysis using a large physical property database ‘Starrydata’. In fact, several quasicrystals ranked nearly first among more than 10,000 samples of various materials (metallic alloys, semiconductors, ceramics, etc.) in terms of the magnitude of the positive temperature coefficient of thermal conductivity. This unique property makes quasicrystals ideal for use in composite thermal diodes. We searched the database for the most suitable materials that can be combined with quasicrystals to create high-performance composite thermal diodes. Analytical calculations using a simple one-dimensional model showed that by selecting the optimal material, a thermal rectification ratio of 3.2 can be obtained. Heat transfer simulations based on the finite element method confirmed that this can be achieved under realistic conditions. This is the highest value of the thermal rectification ratio reported to date for a solid-state composite thermal diode.